Use of EPANET Software in Network Planning for Drinking Water Supply Systems in Balikpapan Tengah District and Balikpapan City District - Nia Febrianti; Dwi Arief Prambudi (Journal of Multidisciplinary Science, 2023)
Clean water is a primary need for everyone. The need for clean water will increase over time as well as the increase in population, this makes it necessary to carry out an assessment related to water demand in the future up to 10 years in the future. Therefore, considering the raw water source whose availability cannot be predicted so that it can be calculated the need for clean water for the District of Balikpapan Tengah and Balikpapan City, the water demand value is obtained, namely the debit in the District of Central Balikpapan is 352 liters/second and the District of Balikpapan Kota is 295 liters. /second. After that, an analysis of the drinking water distribution routing network was carried out using the Hardy-Cross method and the use of EPANET 2.0 software. Then calculations are carried out by entering data in the form of needs data such as maps of the main pipeline network, 24-hour flow patterns, and data related to contours or elevation. In terms of speed and accuracy of analysis using EPANET 2.0 software for drinking water supply systems is considered more fulfilling.